THE EFFECT OF THE USE OF IMAGE CARD MEDIA ON SHORT STORY WRITING ABILITY - Agus Sulaeman; Enawar Enawar (STIBA IEC JAKARTA, 2022)
The purpose of this study was to analyze the differences in students' Indonesian writing skills in short stories material who received flash cards and students who received conventional learning methods. The population in this study was class VIII SMP Aruslan, Sukamulya District, Tangerang Regency, for the 2021/2022 academic year. The sample in this study were students of class VIII.3 and VIII.4 totaling 60 students with a sampling technique using purposive sampling, two classes were selected, namely the experimental group and the control group. The experimental group received a picture card learning media (flash card), while the control group received conventional learning. The method used in this study is a quasi-experimental method with a nonequivalent control group design. The research instrument given was in the form of a test consisting of 10 questions in the form of an essay. Analysis prerequisite test using Chi Square test and Fisher's exact test, it was found that both samples were normally distributed and homogeneous. From the calculation of statistical tests obtained tcount > ttable (2, 48 > 1.99), then Ho is rejected and H1 is accepted at a significant level = 0.05 with degrees of freedom (db) = 64. So it can be concluded that there are differences in students' short story writing abilities. which is taught with the media of picture cards (flash card) and which is taught by conventional learning methods. Thus, it can be concluded that there is an effect of using flash card media on students' short story writing skills.